Model Rencana Produksi Kaca Otomotif Dengan Metode Klasifikasi ABC Untuk Menurunkan Tingkat Persediaan (Studi kasus di PT. Asahimas Flat Glass, Tbk.) - Agus Ruhimat (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
The paper discusses about the model of production plan for automotive glasses using the ABC classification method to reduce the supply level. The step being taken in this research is to classify each glass size based on each class and calculate the weight of primary factors influencing the accumulation of supply in form of cash value, risk of under supply and accuracy of estimate. The model of proposed production planning is based on the ABC classification method, and the result could direct the planning officer to conduct the different handling of supply for all glass sizes based on their actual condition. Using this model, we obtain the realistic figure of supply level according to the needs and after being verified the figure can be reduced and the model cab be applied. In this paper, we also conduct case study in a main producer of automotive glass in Indonesia, which is PT. AMG Tbk., which hereinafter is called AMG. AMG is a primary producer for automotive glass in Indonesia with a market share accounting for more than 80%. Currently, almost all automotive industries implement Lean concept which among other is known as Kanban system where the incoming goods should exact, either in time and in the quantity. AMG as the supplier of automotive glasses should anticipate the risk of under supply because of the lack of estimate accuracy or reliability of the production process; so far the production planning officer has set the policy in the supply level of 1,3 month in the end of the current month for all glass sizes with average value of supply per month reaching 20 billions rupiah. The figure is too big because it is the retained cash flow, so that the level of supply for 1.3 month should be reviewed